2008
DOI: 10.1002/cncr.23968
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patient preferences for quality and length of life

Abstract: BACKGROUND. Optimal patient decision making requires integration of patient values, goals, and preferences with information received from the physician. In the case of a life‐threatening illness such as cancer, the weights placed on quality of life (QOL) and length of life (LOL) represent critical values. The objective of the current study was to describe cancer patient values regarding QOL and LOL and explore associations with communication preferences. METHODS. Patients with advanced cancer completed a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
154
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(164 citation statements)
references
References 43 publications
6
154
3
1
Order By: Relevance
“…Increasing age results in rising rates of comorbidity and frailty [2] so tolerance to some standard breast cancer therapies may decrease [3] and older patients may prioritise quality of life over quantity [4]. Consequently, older patients with operable breast cancer may be offered alternative treatment modalities, such as primary endocrine therapy (PET) [5,6], where oestrogen receptor (ER) positive disease is treated with endocrine therapy alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing age results in rising rates of comorbidity and frailty [2] so tolerance to some standard breast cancer therapies may decrease [3] and older patients may prioritise quality of life over quantity [4]. Consequently, older patients with operable breast cancer may be offered alternative treatment modalities, such as primary endocrine therapy (PET) [5,6], where oestrogen receptor (ER) positive disease is treated with endocrine therapy alone.…”
mentioning
confidence: 99%
“…Evidence suggests that elderly patients may prioritise quality of life over quantity [4] and patient choice is commonly stated as a reason for treating patients with PET [10,20]. However, a recent study by Lavelle and colleagues [23] found that lower rates of surgical treatment are unlikely to be due to patient choice and these results suggest that UK HCPs agree with this, believing that patients would not choose non-operative management if given the option.…”
mentioning
confidence: 99%
“…Meropol et al (2008) indicated if the clinician knows the patient's preferences, communication is improved and distress is lessened, supporting the use of QOL assessments to facilitate communication [23]. Rummans et al (2006) utilized a multi-disciplinary psychosocial intervention, which encouraged patients to communicate needs and results indicated a short-term improvement in overall QOL (p=0.047) and spirituality (p=0.003) [24].…”
Section: Discussionmentioning
confidence: 99%
“…These treatment options may include standard therapy or experimental approaches, as well as supportive care. [32] In this case, the patient's preference is important. Bioethics supports incorporating patients in their own medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In studies. [32,[34][35][36] In which patients were asked about their preferences regarding their treatment, the patients whose cancer-related distress was low (such as older patients, male, highly educated and childless patients) preferred quality of life; however, patients who were young and who had a child and a more functional health status preferred the prolongation of life. [34] Instead of trying to protect a patient by not informing him/ her about the cancer diagnosis, we should investigate the ways to inform a patient about his/her cancer diagnosis without causing negative consequences.…”
Section: Discussionmentioning
confidence: 99%